Agave jimenoi (Polycephalae group, Asparagaceae) a new species from the Totonacapan region, Veracruz, Mexico - Cházaro-Basañez, Miguel; Vázquez-García, Jose Antonio (Phytotaxa, 2013)
A new hydrophytic species of Agave from the Tlapacoyan region, Veracruz, Mexico, is described and illustrated. Agave jimenoi belongs to the subgenus Littaea, and to the Polycepahalae group, it differs from A. gomezpompae in its smaller rosettes, hanging stems, leaves and inflorescences and glaucous-green pruinose leaves. A distribution map and key to the species of the Polycephalae group is presented.